2014
DOI: 10.1007/430_2014_147
|View full text |Cite
|
Sign up to set email alerts
|

d10-ML2 Complexes: Structure, Bonding, and Catalytic Activity

Abstract: Our goal in this chapter is to show how one can obtain a better understanding of the decisive factors for the selectivity and efficiency of catalytically active metal complexes. This ongoing research project has been designated the 'Fragment-oriented Design of Catalysts' and aims at providing design principles for a more rational development of catalysts. To this end, we have performed a series of studies in which we systematically investigate the effect of a specific variation on the reactivity of the catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 86 publications
1
16
0
Order By: Relevance
“…Yet, one may wonder why bending Ni(PH 3 ) 2 is more feasible than bending, for example, Pd(PH 3 ) 2 . This issue has been addressed in a study on a large set of d 10 ‐ML 2 catalyst complexes . The systematic approach taken revealed a number of interesting trends, which we will address using two representative series, namely Rh(PH 3 ) 2 − , Pd(PH 3 ) 2 , Ag(PH 3 ) 2 + in which the metal center is varied, and Pd(NH 3 ) 2 , Pd(PH 3 ) 2 , Pd(CO) 2 in which the ligand is varied.…”
Section: Selected Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, one may wonder why bending Ni(PH 3 ) 2 is more feasible than bending, for example, Pd(PH 3 ) 2 . This issue has been addressed in a study on a large set of d 10 ‐ML 2 catalyst complexes . The systematic approach taken revealed a number of interesting trends, which we will address using two representative series, namely Rh(PH 3 ) 2 − , Pd(PH 3 ) 2 , Ag(PH 3 ) 2 + in which the metal center is varied, and Pd(NH 3 ) 2 , Pd(PH 3 ) 2 , Pd(CO) 2 in which the ligand is varied.…”
Section: Selected Applicationsmentioning
confidence: 99%
“…This issue has been addressed in a study on a large set of d 10 -ML 2 catalyst complexes. 46,87 The systematic approach taken revealed a number of interesting trends, which we will address using two representative series, namely Rh(PH 3 ) 2 − , Pd(PH 3 ) 2 , Ag(PH 3 ) 2 + in which the metal center is varied, and Pd(NH 3 ) 2 , Pd(PH 3 ) 2 , Pd(CO) 2 in which the ligand is varied. It is found that the bite angle becomes less flexible when the metal center is varied from Ag + to Rh − , and increasingly flexible from Pd(NH 3 ) 2 to Pd(CO) 2 .…”
Section: Bite Angles and Their Flexibility In Transition Metal-mediatmentioning
confidence: 99%
See 2 more Smart Citations
“…The past few decades have witnessed an increasing interest in the chemistry of d 10 metal systems because of their rich photochemical properties, [1] catalytic applications [2] PPh 2 py/2-methylpyridine (mpy) and P(4-FPh) 3 /mpy complexes, wherein centrosymmetric dimers with eight-membered central rings are obtained: [(R 3 P)(mpy)Cu(NCS) 2 -Cu(PR 3 )(mpy)], as is also the case in the parent 1:2 CuNCS/ PPh 2 py adduct [(pyPh 2 P) 2 Cu(NCS) 2 Cu(PPh 2 py) 2 ]. For the 1:1:1 CuNCS/P(4-FPh) 3 /py and PPh 3 /Brmpy (Brmpy = 3bromo-4-methylpyridine) adducts, and, likely, CuNCS/ PPh 2 py/py (1:1:1), single-stranded polymers of the form [···Cu(NCS)(PR 3 )(py-base) (Cu)···] (ϱ|ϱ) with linearly bridging NCS ligands were obtained.…”
Section: Introductionmentioning
confidence: 99%